MUSIK SEBAGAI METODE KRITIK SOSIAL-POLITIK (Analisis Perlawanan dalam Tiga Lagu Iwan Fals pada Masa Orde Baru) - Wiyanti, Zalsa Pramudya; -, Nur Hidayat -; -, Wijayanto - (Journal of Politic and Government Studies, 2024)
The phenomenon of Iwan Fals' protest music as symbolic resistance and part of the new social movement is intriguing to explore. During the New Order era, restrictions on criticism, such as media censorship, limitations on student activities via NKK/BKK, and gathering bans, reduced the space for civil society to voice opposition to the government. Iwan Fals, a mainstream musician, actively criticized the regime through protest songs like “Tikus-Tikus Kantor” and “Ambulans Zig-Zag.” His songs, such as “Suara Buat Wakil Rakyat,” were often used during demonstrations. Iwan Fals faced censorship from the regime for being perceived as